The normativity of communication Norms and Ideals in Peirce's Speculative Rhetoric - Redondo, Ignacio (Normative thought of charles s. peirce, 2020)
The normativity of communication Norms and Ideals in Peirce's Speculative Rhetoric
Keywords: normativity of communication; rhetoric; WOS(2); Scopus(2)